Role Of Inhaled Nitric Oxides In Pregnancy With Eisenmenger Syndrome - Muhammad Anas; Nenny Triastuti; Muhammad Perdana Airlangga (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2020)
ABSTRACTEisenmenger Syndrome (ES) is congenital heart disease with pulmonary hypertension and shunting turning from right to left. The resistance of pulmonary vascular more than 7.5 mmHg/L/min. The right ventricle and pulmonary artery always enlarge. During pregnancy, there will be hemodynamic changes that will affect the ES. It can be understood the possible dangers that can occur, like right heart failure; an increase in pulmonary arteries or the aggravation of pulmonary hypertension because there is no decrease in pulmonary resistance; A sudden decrease in venous return in supine hypotension syndrome can cause a relative increase in pulmonary arterial pressure so as to aggravate pulmonary hypertension and reverse shunting.Physiological effects of inhaled nitric oxide (INO) therapy cause selective pulmonary vasodilation: Hypoxia alveoli causes reversible vasoconstriction, thereby increasing pulmonary wedge pressure. INO can lower it. Moderate cardiac output and systematic arterial pressure are not affected; Selective in pulmonary because it is activated by hemoglobin; Selective vasodilation in the ventilated area, local hypoxia alveoli constricts the surrounding vascular tissue and redistributes blood flow to the ventilated lungs better and higher intraalveolar oxygen pressure. INO enhances this mechanism by increasing blood flow through a well-ventilated lung; Bronchodilators; Pulmonary surfactant, The combination of high concentrations of inspired oxygen and high concentrations of INO reduces the minimum surfactant surface tension.Keywords: Inhalation Nitric Oxides, Pregnancy, Eisenmenger Syndrome